Performance Evaluation of Selenite (SeO32−) Reduction by Enterococcus spp. - Job T. Tendenedzai (Catalysts, 2021)
Lactic acid bacteria (LAB) such as Enterococcus spp. have an advantage over several bacteria because of their ability to easily adapt to extreme conditions which include high temperatures, highly acidic or alkaline conditions and toxic metals. Although many microorganisms have been shown to reduce selenite (SeO32−) to elemental selenium (Se0), not much work has been done on the combined effect of Enterococcus spp. In this study, aerobic batch reduction of different selenite concentrations (1, 3 and 5 mM) was conducted using Enterococcus hermanniensis sp. and Enterococcus gallinarum sp. (3.5 h, 35 ± 2 °C, starting pH > 8.5). Results from the experiments showed that the average reductions rates were 0.608, 1.921 and 3.238 mmol·(L·h)−1, for the 1, 3 and 5 mM SeO32− concentrations respectively. In addition, more selenite was reduced for the 5 mM concentration compared to the 1 and 3 mM concentrations albeit constant biomass being used for all experiments. Other parameters which were monitored were the glucose consumption rate, protein variation, pH and ORP (oxidation reduction potential). TEM analysis was also conducted and it showed the location of electron-dense selenium nanoparticles (SeNPs). From the results obtained in this study, the authors concluded that Enterococcus species’s high adaptability makes it suitable for rapid selenium reduction and biosynthesis of elemental selenium.